A unique juxtaglomerular apparatus in the river ray, Potamotrygon humerosa, a freshwater stingray - Lacy, E. R.; Reale, E. (Zoomorphology, 2018)
The microscopic architecture of the juxtaglomerular apparatus (JGA) of the renal corpuscle of a stenohaline freshwater stingray, the river ray ( Potamotrygon humerosa) , was studied using light microscopy of histologic sections, three-dimensional reconstruction using 1 micron epoxy resin serial sections and transmission electron microscopy. The glomeruli studied were located medially in the kidney and had a single afferent arteriole but multiple, up to 11, efferent arterioles which exited the glomerular capillary loops along a deep indentation, termed vascular groove, of Bowman’s capsule. This groove extended from the afferent arteriole to the urinary pole where the renal tubule began. In this groove lay the distal tubule in contact with the glomerular mesangium and covering the multiple efferent arterioles. This portion of the distal tubule had specialized epithelial cells, the macula densa , typical of those in JGAs of all other phylogenetic groups. Along the entire groove on the inside of Bowman’s capsule lay the transition of the parietal to visceral epithelium where specialized cells, peripolar cells, were present. Granules in these peripolar cells were present only at the epithelial transition adjacent to the afferent arteriole and not adjacent to the efferent arterioles. In conclusion, the unique anatomical JGA in a population of river ray renal corpuscles suggests they have a different function in the glomerular feedback system than that classically described in mammals. Considering that in the same river ray kidney there are other populations of glomeruli which possess the classically described JGA and also that there are newly forming glomeruli suggest that a spectrum of differing glomerular function exists within each kidney.